The Research on Impulsive Events in Railway Noise Generated During Passage Through a Railroad Switch - Bartłomiej KUKULSKI; Tadeusz WSZOŁEK (Archives of Acoustics)
This paper presents the result of research on the impulsive components of a railway noise generated during passage through a railroad switch compared with a typical rail noise and evaluation of this phenomenon with particular emphasis on impulsive sounds. The study includes the analysis of the source of impulsive components in the railway noise, the methodology of measurement and data analysis. Spectral analysis of typical fragments passing through a railroad switch is given together with a proposal of additional indicators to assess the noise. Authors propose three descriptors of the impulsive noise such as spectral centroid, kurtosis and impulsiveness, and show that these descriptors can be useful in assessment of the impulsive noise generated during trains’ crossing.